Developing a pilot test for an empirical research on managerial competency in Thailand's public health sector - Chutipattana, Nirachon; Sharif, Mohmad Yazam; Mohd Shamsudin, Faridahwati (2008)
The aim of this paper is to show the process of conducting a pilot test on rural managers’ managerial competency conducted in the primary healthcare units in Patthalung- a province in southern Thailand. This paper explains the justification process of developing the instrument prior to the main doctoral study. The instrument comprises five parts - personality, motivation, organizational culture, managerial competency, and respondent’s personal background. The pilot testing process was divided into six steps respectively; firstly, the researcher asked one bilingual expert to translate the questionnaire from English to Thai language. Then, the managerial competency elements were cross-checked with the heads of department of the Provincial Public Health Office in Thailand’s Songkhla Province. Next, five experts in healthcare industry were asked to critique the instrument. After that, three primary care unit managers were randomly selected to read and answer the full set of questions as well as to validate its content in line with the Thai culture. After that, the researcher asked another bilingual expert to translate the said questionnaire back from Thai into English. Finally, 110 questionnaires were mailed to public health managers in Patthalung province and they then were analyzed using the mean and percentage methods. The techniques that were used for developing the instrument were the Delphi technique, the small group technique, the forward translation, the back translation, the survey technique, and the telephone interview. Overall, the researchers believe that the pilot test had helped to improve the quality and the efficiency of the instrument in determining the managerial competencies of primary care unit managers.